2001
DOI: 10.1046/j.1523-1755.2001.0590051739.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of renal proximal tubular epithelial cell hyaluronan generation: Implications for diabetic nephropathy

Abstract: This study demonstrates, to our knowledge for the first time, that increased HA synthesis in response to either IL-1 beta or elevated 25 mmol/L D-glucose is associated with NF-kappa B-activated transcription of HAS2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 35 publications
5
65
1
1
Order By: Relevance
“…Finally, exposure to high glucose concentrations also increases hyaluronan synthesis in renal proximal tubular cells (15), in renal interstitial fibroblasts (16), and in vascular smooth muscle cells (17). Thus, the broader implications of this model for diabetic pathology become clearer.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, exposure to high glucose concentrations also increases hyaluronan synthesis in renal proximal tubular cells (15), in renal interstitial fibroblasts (16), and in vascular smooth muscle cells (17). Thus, the broader implications of this model for diabetic pathology become clearer.…”
Section: Figmentioning
confidence: 94%
“…Previous studies have shown increased hyaluronan content in glomeruli isolated from diabetic animals (13) and in mesangial cells cultured in medium with a high glucose concentration (14). Exposure to high glucose concentrations also increases hyaluronan synthesis in renal proximal tubular cells (15), in renal interstitial fibroblasts (16), and in vascular smooth muscle cells (17), all of which are involved in normal kidney physiology.…”
mentioning
confidence: 94%
“…We have previously demonstrated that IL-1␤ is a potent stimulus for HA synthesis as assessed by quantitation of HA in the cell culture supernatant of IL-1␤-treated PTC (10). We therefore sought to determine the effect of IL-1␤ on HA cable formation and monocyte binding in HK2 cells.…”
Section: Il-1␤ Induced Ha Synthesis But Does Not Increase Ha Cable Fomentioning
confidence: 99%
“…We recently examined the regulation of HA synthesis by renal PTC in vitro under conditions that mimic the diabetic state (10). These studies demonstrate that exposure of PTC to elevated D-glucose concentrations leads to nuclear factor-B (NF-B)-dependent transcriptional activation of the HA synthase HAS2 and stimulation of HA synthesis.…”
mentioning
confidence: 99%
“…End stage renal failure is most frequently characterized by progressive interstitial fibrosis and tubular atrophy (10), and increased expression of HA in the renal corticointerstitium is associated with this progression (11,12). In high glucose concentrations, which mimic diabetic nephropathy, renal proximal tubular epithelial cells synthesize high levels of HA, which is coincident with specific up-regulation of transcription at the HAS2 locus (13). The mesothelial cells that line the peritoneal membrane synthesize HA as a normal constituent of human peritoneal effluent, and this synthesis is up-regulated during periods of peritonitis in patients undergoing peritoneal dialysis (14).…”
mentioning
confidence: 99%